Antimicrobial properties of selected microalgae exopolysaccharide-enriched extracts: influence of antimicrobial assays and targeted microorganisms - Pointcheval, Marion; Massé, Anthony; Floc’hlay, David; Chanonat, Franck; Estival, Jacques; Durand, Marie-José (Frontiers in Microbiology, 2025)
Exopolysaccharide (EPS)-enriched extracts derived from microalgae exhibit a wide range of bioactive properties, including antibacterial and antifungal properties. However, these properties vary depending on the microalgae species, the antimicrobial assay used, and selected targeted microorganisms. This study offers to investigate the antimicrobial properties of exopolysaccharide-enriched extracts obtained from five microalgae species scarcely studied in this context. The targeted microorganisms selected for this study included Gram-positive (Bacillus subtilis) and Gram-negative bacteria (Pseudomonas aeruginosa), fungi (Cladosporium cladosporioides), and microalgae (Chlorella vulgaris). Well-diffusion assay, broth microdilution assay, and growth measurements using absorbance were used to compare the methods and fully estimate the antimicrobial properties. Using absorbance measurements, growth rate inhibitions of at least 80% were observed on all targeted species for at least one microalgal EPS-enriched extract. At a concentration of 500 mgGlcEq · L−1, most active extracts of B. subtilis were obtained from Chlamydomonas reinhardtii (87.1% of growth inhibition), Nostoc commune (53.7%), and Eustigmatos polyphem (46.4%). EPS-enriched extracts from C. reinhardtii (86.2%), N. commune (59.9%), and Porphyridium cruentum (31.1%) were found to be the most effective against P. aeruginosa. Antifungal activities were the highest for EPS extracts from Microchloropsis gaditana (86.0%), C. reinhardtii (16.6%), and E. polyphem (17.8%). The results indicated microalgae growth inhibition by EPS-enriched extracts from N. commune (99.3%), C. reinhardtii (84.8%), and M. gaditana (84.1%). To our knowledge, this study is the first to explore the algicidal properties of EPS-enriched extracts derived from microalgae, identifying promising candidates for future investigations into their potential applications.